Evaluation of Site Effects in Adra Town (southern Spain) - Vidal, F.; Navarro, M.; Alcalá García, F.J.; Enomoto, T.; Abeki, N.; Sánchez, F.J. (Física de la Tierra, 2002)
Recent destructive earthquakes have shown that damage distribution is generally related to soil typology, large differences being noticed in the level of damage for relatively short distances. In order to evaluate the site effects in Adra town (southern Spain), geological and geomorphological survey and microtremor measurements were carried out. The geologic materials have been classified according to their seismic amplification capacity. To achieve this goal, basic geological and geotechnical characteristics have been determined (N-values for the SPT tests and density), identifying the nature of the material and obtaining the calculated values of the S wave velocity (Vs). Measurements of short-period microtremors were performed in and around the town, and Nakamura’s method was applied to determine a predominant period distribution map. The predominant period range is from 0.1s in rock site (northern part of the town) to more than 0.5s at soft soil site (southern part of the town). These results will be used in the evaluation of ground dynamic properties and will be included in seismic microzoning of Adra town.